LEXICAL COVERAGE AND INCIDENTAL LEARNING POTENTIAL IN ENGLISH TEXTBOOKS FOR VIETNAMESE TERTIARY EFL LEARNERS (Journal of Foreign Language Studies, 2025)
This study presents a corpus-based analysis of the vocabulary coverage in the reading texts of the “Inside Reading” series used by students at a Vietnamese university. It examines the lexical profile of the reading texts and evaluates the recurrence of unfamiliar vocabulary items to determine the extent to which these texts support incidental vocabulary acquisition. The reading passages were processed unsing the Vocabprofilers on the Lextutor.ca website and compared with the results of Vocabulary Size Test administered to 86 students to estimate their vocabulary size. The findings reveal that 95% lexical coverage was achieved with the first 4,000 most frequent words while the optimal 98% coverage was reached with 6,000 words. Given the participants’ average receptive vocabulary size of approximately 8,000 words, the findings indicate that the texts match their proficiency level. However, unfamiliar word families rarely reoccur. While the reading materials support comprehension, they offer limited opportunities for the reinforcement of new vocabulary. These findings provide implications for textbook designers and language teachers.
Keywords: corpus; vocabulary repetition; incidental vocabulary learning; vocabulary coverage; vocabulary threshold